Analysis of Determinants of Beef Production and Imports and Their Impact on Beef Consumption in Indonesia - Mire, Muhammad Saleh; Suharto , Rahcmad Budi (International Journal of Scientific Research and Management (IJSRM), 2024)
https://docs.google.com/document/d/1zcLan_8D1labNXtmVnjiD3E5e5wHfmyG/edit